Jet rates at small x to single-logarithmic accuracy - Ewerz, Carlo; Webber, Bryan R. (Journal of high energy physics, 1999)
We present predictions of jet rates in deep inelastic scattering at small x to leading-logarithmic order in x , including all sub-leading logarithms of Q 2 /μ R 2 where μ R is the transverse momentum scale at which jets are resolved. We give explicit results for up to three jets, and a perturbative expansion for multi-jet rates and jet multiplicities.